MENINGKATKAN MINAT DAN HASIL BELAJAR SISWA PADA SUBTEMA HEWAN DAN SEKITARKU DENGAN MENGGUNAKAN METODE PICTURE AND PICTURE DI KELAS II SD NEGERI 101070 SIUNGGAM T.A 2020/2021 - Eko Sucahyo; Lismawarni Siregar; Fitriani Harahap; Sartika Ratih Asmara Nasution (Jurnal Ilmiah Pendidikan Dasar (JIPDAS), 2023)
Based on the results of observations in class II SD Negeri 101070 Siunggam, found problems in learning, including low teacher skills, low student interest, and low student learning outcomes. To overcome these problems, the Picture and Picture method was applied in learning Theme 7 Sub-theme 1 Animals and My Surroundings. The purpose of this study is to improve teacher skills, increase student interest, and improve student learning outcomes through the application of the Picture and Picture method. This action research was carried out in two research cycles, each cycle of 2 meetings. The subjects of this study were teachers and 24 second grade students at SDN 101070 Siunggam. The research data in the form of quantitative data and qualitative data were analyzed using descriptive analysis techniques. The variables of this research are (1) teacher skills, (2) student interest, and (3) learning outcomes. From the results of the study, it can be seen that: (1) teacher skills in the first cycle of the first meeting obtained a score of 23 sufficient criteria and in the first cycle of the second meeting a score of 30 good criteria was obtained. For the second cycle of the first meeting, 34 very good criteria were obtained and for the second cycle of the second meeting, 38 very good criteria was obtained. For the second cycle of the first meeting, 34 very good criteria were obtained and for the second cycle of the second meeting, 38 very good criteria were obtained, (2) student interest in the first cycle was 89 (74.17%) in the medium category, then increased in the second cycle. with a score of 103 (85.83) in the high category, (3) student learning outcomes at the end of the first cycle obtained an average value of 71.87 and classical learning completeness 66.67%, at the end of the second cycle an average score of 80, 42 and classical learning completeness of 91.67%. The conclusion of this study is that the application of the Picture and Picture method can improve teacher skills, student interests, and student learning outcomes for class II SDN 101070 Siunggam. The suggestion of this research is that teachers should get used to applying the Picture and Picture method in learning in lower classes as an effort to improve results student learning and student interest in participating in learning activities.   Berdasarkan hasil observasi di kelas II SD Negeri 101070 Siunggam, ditemukan permasalahan dalam pembelajaran, diantaranya keterampilan guru rendah, minat siswa rendah, dan hasil belajar siswa rendah. Untuk mengatasi permasalahan tersebut, diterapkan metode Picture and Picture dalam pembelajaran Tema 7 Subtema 1 Hewan dan Sekitarku. Tujuan dari penelitian ini adalah untuk meningkatkan keterampilan guru, meningkatkan minat siswa, dan meningkatkan hasil belajar siswa melalui penerapan metode Picture and Picture. Penelitian tindakan ini dilaksanakan dalam dua siklus penelitian, masing-masing siklus 2 pertemuan. Subjek penelitian ini adalah guru dan 24 siswa kelas II SDN 101070 Siunggam. Data hasil penelitian berupa data kuantitatif dan data kualitatif yang dianalisis menggunakan teknik analisis deskriptif. Variabel penelitian ini adalah (1) keterampilan guru, (2) minat siswa, dan (3) hasil belajar. Dari hasil penelitian dapat diketahui bahwa: (1) keterampilan guru pada siklus I pertemuan I diperoleh skor 23 kriteria cukup dan pada siklus I pertemuan II diperoleh skor 30 kriteria baik. Untuk siklus II pertemuan I diperoleh skor 34 kriteria sangat baik dan untuk siklus II pertemuan II diperoleh skor 38 kriteria sangat baik, (2) minat siswa pada siklus I memperoleh jumlah 89 (74,17%) pada kategori sedang, kemudian meningkat pada siklus II dengan skor 103 (85,83) pada kategori tinggi, (3) hasil belajar siswa pada akhir siklus I memperoleh nilai rata-rata 71,87 dan ketuntasan belajar klasikal 66,67%, pada akhir siklus II mendapat nilai rata-rata 80,42 dan ketuntasan belajar klasikal sebesar 91,67%. Simpulan penelitian ini adalah penerapan metode Picture and Picture dapat meningkatkan keterampilan guru, minat siswa, dan hasil belajar siswa kelas II SDN 101070 Siunggam.. Saran penelitian ini adalah guru sebaiknya membiasakan menerapkan metode Picture and Picture dalam pembelajaran di kelas rendah sebagai upaya untuk meningkatkan hasil belajar siswa dan minat siswa dalam mengikuti kegiatan pembelajaran.